UV-blocking ZnO nanostructure anti-reflective coatings - Du, Qing Guo (2013)
In this paper, we apply finite difference time domain simulation to determine the absorptance and reflectance of ZnO nanowire and nanohole array structures for an efficient UV-blocking anti-reflective coating. Comparing to ZnO thin films, both nanowires and nanoholes have much improved performance. ZnO nanowires and nanoholes have similar absorptions in the UV range. However, ZnO nanowires have lower absorptance than nanoholes in the visible range. Influences of different parameters including lattice constant a, ZnO filling ratio f and nanowire heights h are analyzed. The optical properties of the nanostructures are less dependent on the incident angle of light, which enables them to be used as wide angle anti-reflective coatings with UV blocking.